(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In today’s world, nearly everyone is using Facebook, twitter and LinkedIn. Social media helps individuals to attach, share ideas, content, info etc. It’s having huge impact on education further. It’s additionally an enormous a part of students. Students and academics remains connected with one another on social media to share info and are having an honest use of it. Professors are victimization social media to host live lectures and also are giving support for drawback determination. Professors also are victimization social media for branding professionally and making a reputation for them.